Antioxidant activity and peptidomic analysis of porcine liver hydrolysates using alcalase, bromelain, flavourzyme and papain enzymes. (November 2020) - López-Pedrouso, María; Borrajo, Paula; Pateiro, Mirian; Lorenzo, José M.; Franco, Daniel
Graphical abstract: Highlights: Pork liver used to prepare hydrolysates is rich in proteins. Enzymatic hydrolysates of pork liver generated antioxidant peptides. Peptidomic patterns from alcalase, bromelain, papain and flavourzyme were different. The most abundant five peptides were strongly correlated with antioxidant capacity. Abstract: Antioxidant peptides are increasingly being recognized as food additives due to their effects on body human, regulating in vivo oxidative stress against oxidation of lipids and proteins. Meat by-products are rich sources of protein that can be employed for this purpose. Specifically, porcine liver can be used to prepare hydrolysates with antioxidant activity employing proteolytic enzymes such as alcalase, bromelain, papain and flavourzyme. In this study, the antioxidant activity of these four porcine liver hydrolysates was evaluated by 2, 2-diphenyl-1-picrylhydrazyl (DPPH), ((2, 2-azinobis-(3-ethyl-benzothiazoline-6-sulphonate) (ABTS), Ferric reducing antioxidant power assay (FRAP) and Oxygen radical absorbance capacity assay (ORAC) assays and the identification of bioactive peptides was carried out by SWATH-MS technology. According to the SDS-PAGE pattern, the proteolysis index and the free amino acids amount, the protein degradation was clearly different among the studied enzymes. Indeed, alcalase enzyme produced the release of small peptides, meanwhile flavourzyme produced higher level of free amino acids. The heatmap analysis showed a peptidomic pattern more differentiated for alcalase than for the other enzymes. The peptides most abundant and correlated with antioxidant capacity were APAAIGPYSQAVLVDR from uncharacterized protein, GLNQALVDLHALGSAR, ALFQDVQKPSQDEWGK and LSGPQAGLGEYLFER from ferritin and LGEHNIDVLEGNEQFINAAK from trypsinogen. The production and characterization of biopeptides is a new merging challenge of meat industry.